DYNAMICS OF SOCIAL CONFLICT IN BENER DAM AND MINING PLAN DEVELOPMENT IN WADAS VILLAGE: KARL MARX'S CONFLICT THEORY PERSPECTIVE - Fina Nayla Farha; Restu Tria Anugrah; Syahwa Putri Restivalia; Zaematul Mahbubah; Salma Putri Adani; Didi Pramono (Universitas Negeri Medan, 2022)
The majority of people in Wadas Village work as farmers who use natural resource to support their daily life. The commodities of the Wadas Village area are able to encourage their economic welfare. By the time, the welfare of the community has been disturbed by the planning of building the Bener Dam which exploits andesite stones from Wadas Village. This condition triggers conflict between the local community, the government and also the police. The purpose of this discussion is to review the development plan and the dynamics of social conflict in the plan for the construction of the Bener Dam and ansesite stones mining in Wadas Village which is viewed from the conflict theory of Karl Marx. The method of this research is a qualitative descriptive method with a literature study approach. The results of the study found that the people of Wadas Village refused andesite mining as a material for the Bener Dam because it threatens water sources and erodes agricultural land which is used as an economic source. From the perspective of Karl Marx, the conflict was seen government as the bourgeoisie and the people of Wadas Village as the proletariat. The conclusion from the results of this discussion is that the construction of the Bener Dam creates pros and cons between the community and the government, as well as the opportunity for the formation of social classes that can be studied through Karl Marx's theory of conflict.